Pre‐Plated Cell Lines for ADMETox Applications in the Pharmaceutical Industry. Issue 1 (6th August 2015) - Torres, Francisco M.; Sáfár, Zsolt; Vázquez‐Sánchez, Maria A.; Kurunczi, Anita; Kis, Emese; Magnan, Rémi; Jani, Márton; Nicolás, Oriol; Krajcsi, Péter
Abstract: Membrane transporters significantly modulate membrane permeability of endobiotics and xenobiotics, such as bile acids and drugs, respectively. Various in vitro methods have been established for both ATP‐binding cassette (ABC) transporters to examine cellular efflux and uptake, and for solute carriers (SLC) to examine cellular uptake of substrates. Cell‐based systems are the models of choice to test drug‐transporter interactions as well as drug‐drug interactions for research and regulatory purposes, albeit, for low passive permeability substrates of ABC transporters, vesicular uptake assays are also recommended. Commercially available pre‐plated cells (e.g., immortalized or transfected) offer a useful alternative to in‐house cell culture. Three main methods are known to manufacture pre‐plated cultures: regular culture medium with vacuum seal, cryopreserved delivery, and the solid shipping media technology. The regular culture medium and the solid shipping media technologies provide ready‐to‐use models for end users. Models expressing a broad selection of transporters are available in pre‐plated formats for absorption, distribution, metabolism, excretion, and toxicity (ADMETox) studies. Conversely, the application and utility of pre‐plated cultures coupled with personal experiences have not been extensively covered in published research papers or reviews, despite availability and significant use of pre‐plated products in the pharmaceutical industry. In this overview, we will briefly describe: 1) in vitro tools commonly used for ADMETox testing; 2) methods employed in manufacturing, shipment and preparation of pre‐plated cell lines; 3) cell‐membrane barrier models currently available in pre‐plated format to reproduce passage restriction of physiological barriers to certain compounds; and 4) recommended pre‐plated cell lines overexpressing uptake transporters for ADMETox applications. © 2015 by John Wiley & Sons, Inc.